Peranan Pengetua dalam Pembangunan Staf - Mokhtar, Abdullah (1996)
The Principal is appointed by Ministry Of Education, Malaysia to be the head of teacher and non-teaching staff in a secondary school. Staff development in the school is part of the duty and responsibility of the principal. The objective of this study is to explore or identify the extent of principal’s role in staff development. This study will investigate: 1) Principal’s understanding of the concept, aim, objective and benefits in staff development; 2) Principal’s perception of the assisting and restricting factors in staff development; 3) Principal’s understanding in evaluation of staff development and the relation of staff appraisal with staff development; 4) Determine approach and strategy undertaken by the principal in implementing: (a) Need assesment of staff development; (b) Varied activities, technique and situation in staff development; (c) Selection of participants of staff development programs; and, (d) Evaluation of staff development. A random sampling of 65 principal from grade A and grade B secondary school in Pahang where six of the principal selected at random to be interviewed. The instruments of this study consist of non-structural question for interview and a set of self developed questionnaire. Major findings are: (1) Principal have a high level of: (a) Understanding of the aim, objective and benefits in staff development; (b) Understanding of the assisting and restricting factors in staff development; (c) Understanding in evaluation of staff development and the relation of staff appraisal with staff development; (2) Implementation of development is still at the moderate level and: (a) Need assesment is more towards informal approach; (b) Varied types of activities more on internal or in-house training, techniques used more on conventional or traditional approach and situation in SW development focusing to internal or school’s environment; (c) Selection of participants of staff development programs; and, (d) Evaluation of staff development focusing on informal observation and discussion; (3) Understanding and implementation of staff development are not statistically significant based on demographic factors such as school grade, principal grade and gender.